MTH1 inhibitor amplifies the lethality of reactive oxygen species to tumor in photodynamic therapy - Zhao, Lingzhi (2020)
Although photodynamic therapy (PDT) has been clinically applied tumor hypoxia still greatly restricts the performance of this oxygen-dependent oncological treatment. The delivery of oxygen donors to tumor may produce excessive reactive oxygen species (ROS) and damage the peripheral tissues. Herein, we developed a strategy to solve the hypoxia issue by enhancing the lethality of ROS. Before PDT, the ROS-defensing system of the cancer cells was obstructed by an inhibitor to MTH1, which is a key for the remediation of ROS-caused DNA damage. As a result, both nuclei and mitochondrial DNA damages were increased, remarkably promoting cellular apoptosis. The therapeutic results demonstrated that the performance of PDT can be improved by the MTH1 inhibitor, leading to efficient cancer cell killing effect in the hypoxic tumor. This strategy makes better use of the limited oxygen, holding the promise to achieve satisfactory therapeutic effect by PDT without generating redundant cytotoxic ROS.